Efektivitas Penerimaan Retribusi IMB dan Kontribusinya Terhadap PAD - Miftha Rizkina; Nina Andriany Nst; Nur Aliah (Forum Kerjasama Pendidikan Tinggi, 2022)
The purpose of the study was to analyze the effectiveness of IMB retribution receipts in Aceh Barat Daya Regency and its contribution to PAD revenue in Aceh Barat Daya Regency. The method used in this study uses a quantitative descriptive approach regarding the effectiveness of IMB Retribution Receipts based on the facts and data obtained. Primary data was taken through direct observation from observed sources and recorded for the first time at the Investment and One Stop Service Office (DPMPTSP) of Southwest Aceh Regency. Secondary data are summarized from records and documents, as well as archives at the Office of Investment and One Stop Integrated Services (DPMPTSP) of Southwest Aceh Regency. Based on the research that has been done, the results show that from 2017 to 2021 the receipt of IMB retribution is effective even though in 2016 it is less effective. The contribution of the building permit levy from 2016 to 2021 contributed to the relatively small contribution of the Southwest Aceh Regency's Original Revenue